Aferência retiniana e caracterização citoarquitetônica do complexo pulvinar do sagui (Callithrix jacchus): uma análise comparativa entre adultos e idosos - Mendonça, Rayane Bartira Silva do Nascimento (2019)
The pulvinar complex plays a key role in the processing and transmission of information between cortical areas. This nucleus receives inputs from various areas of major sensory systems, such as the cortex, and projects to areas of association of the cerebral cortex, and is thus considered as an associative nucleus. This structure is not identifiable in rodents or other small mammals. However, in primates or pulvinar complex it occupies much of the thalamus and is a component of the subcortical visual system as it receives afferences from the retina and superior colliculus and exhibits the necessary notifications for various areas of the neocortex. Classically, this structure has four subdivisions based on neuronal density and fiber distribution: inferior, medial, lateral and anterior, being the first three involved in visual processing. Senescence includes changes in the organism of a living being, directly related to its evolution in time, without any recognized disease mechanism. Senility, on the other hand, can be defined as conditions that affect the individual throughout his life based on pathophysiological mechanisms. Thus, aging can be characterized as a biological process of decreased physiological function that involves neurological changes associated with cognitive decline, and the individual may be affected by neurodegenerative diseases during advancing age. The marmoset (Callithrix jacchus) is one of the New World primates of daytime habit and visual guidance, which is used in biomedical research because of its phylogenetic proximity to humans. Our objective was to perform a cytoarchitectonic characterization of the pulvinar complex in this species by performing a comparative analysis between two groups: adult and elderly animals, showing their subdivisions and identifying a distribution of neurons, axonal terminals and glial cells and subdivisions of this complex. For this purpose, histochemical and immunohistochemical techniques were used, as well as intraocular injection of neuronal tracker to display as subdivisions, neuronal distribution, glial cells, and currently complex fibers/terminals. All experiments were approved by the Animal Use Ethics Committee of UFRN (CEUA-UFRN Nº. 009.013/2017). Our results confirm the presence of subdivisions in the pulvinar complex in the anterior pulvinar nucleus (APul), medial pulvinar nucleus (MPul), lateral pulvinar nucleus (LPul) and inferior pulvinar nucleus (IPul) presenting the latter four subnuclei: inferior pulvinar centromedial (IpulCM), inferior medial pulvinar (IPulM) and posterior inferior pulvinar (IPulP). The pulvinar complex presents along its rostrocaudal extension, immunoreactive neurons to the specific neuronal nuclear protein (NeuN), the calcium binding protein calbindin (CB), besides glial cells immunoreactive to the glial fibrillar acidic protein (GFAP). Data in elderly animals differ from adult animals, as older animals have a lower intensity of cell labeling in NeuN and CB and a lower intensity of labeling in GFAP. The presence of immunoreactive fibers/terminals in the subunit b of the cholera toxin (CTb) was well evidenced in the IPul only in the medial subnucleus, contralateral to the injected eye, characterizing the presence of direct retinal projection in this nucleus. In older animals, a retinal projection shows discrete when compared to adults animals. Despite being a qualitative study, our data indicate differences between adult and elderly animals, suggesting that the pulvinar complex may suffer a significant loss of functional character during the processing of visual information.